Vocational training as the roundabout route from Abitur to university - Pilz, Matthias [Verfasser] (My University, 2011)
This contribution deals with the double qualification of German "Abitur" holders on the basis of an empirical study. The main research question focuses on the motives of "Abitur" holders who opt (initially) for an apprenticeship rather than going to university. The study is based on a survey conducted among trainees in two training occupations: banking employee (Bankkaufmann/-frau) and insurance employee (Versicherungskaufmann/-frau). (BIBB-Doku)
Keywords: P 2.1.5 Fachhochschul- und Hochschulreife; P 2.3 Auszubildende; S 6.4.1.2 Dienstleistungskaufleute; G 1.3.2 Bildungsverhalten und -verläufe; S 1.3.4 Doppelqualifizierende Bildungsgänge; T 3.4 Befragung; Abiturient; Auszubildender; Bankkaufmann; Versicherungskaufmann; Bildungsverhalten; Ausbildungsentscheidung; Doppelqualifikation; Befragung